Apple-marigold intercropping improves soil properties by changing soil metabolomics and bacterial community structures - Xue, Xiaomin; Chen, Ru; Xu, Chao; Zhang, Chunxiang; Dong, Lijuan; Zhao, Xianyan; Wang, Xiaohan (Frontiers in Microbiology, 2023)
Marigold can protect crops against soil-borne diseases. However, the effects of intercropping with marigold on apple rhizosphere soils are not known. In this study, we investigated the metabolite profiles and bacterial community structures in rhizosphere soils of the apple-marigold intercropping system by high-throughput sequencing and soil metabolomics. The results show that intercropping marigold could significantly enhance soil moisture, nitrogen, and enzyme activities compared with clean tillage. The soil metabolite profiles and the soil bacterial community structures in the rhizosphere soils were different between the inter-and mono-cropping systems. Among nine metabolites, carbohydrates were more increased in the intercropping system than in the monocropping system. Pathway enrichment analysis revealed that the greatest differential, in terms of metabolic pathway, was starch and sucrose metabolism. Moreover, intercropping marigold significantly increased the relative abundance of plant growth promoting bacteria in rhizosphere soils, such as Rhizobiales, Pseudomonadales, and Bacillales. These results indicate that marigold intercropping positively affected the apple orchard’s soil quality and may provide a new intercropping technique to improve soil fertility in orchards and promote plant growth.